Public Health Laboratories Response to SARS-COV-2 Diagnostic Testing during COVID Pandemic in Pakistan: Challenges in Laboratory Diagnosis of COVID-19 in Pakistan - Hasnain Javed; Rimsha Khan; Warda Fatima (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
During COVID-19 Pandemic, diagnostic laboratories played a vital role in outbreak investigation, surveillance, patient monitoring, and therapeutic effectiveness, and hampered the transmission cycle globally. In Pakistan, the health department took an initiative to build BSL-III labs at divisional levels. A qualitative study was conducted among healthcare professionals from 13 major public health national-level laboratories through in-depth interviews with key informants to note down the challenges they faced during the COVID-19 pandemic during diagnostic testing. In this study, 77 % of public health laboratories faced sampling, administrative, and leadership issues. 53 % of laboratories have faced the unavailability of well-trained staff and human resources while both the biosafety and biosecurity protocols, and the lack of resources were compromised in 69 % of labs. Some lab staff (54 %) felt the wastage of resources in terms of excessive testing and fake sampling, while others (54 %) discussed a lack of training and work experience issues. As the majority of the technical lab staff was hired in temporary consultancy mode so 61 % of issues were related to late salaries. 38 % of issues were about fake reporting pressure from higher authorities. 69 % had issues with the continuous supply chain of kits, reagents, PPEs, etc. The work environment was not up to the mark of 69 %. High workload and mental health issues were faced by 92 %, while waste management was 23 %, shortage of lab space for massive testing by 38 %, and stigma and discrimination among healthcare workers and the general public due to involvement in COVID-19 testing were felt by 46 %.